2021
DOI: 10.1249/jsr.0000000000000863
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Supplementation: An Update

Abstract: Creatine is a popular and widely used ergogenic dietary supplement among athletes, for which studies have consistently shown increased lean muscle mass and exercise capacity when used with short-duration, high-intensity exercise. In addition to strength gains, research has shown that creatine supplementation may provide additional benefits including enhanced postexercise recovery, injury prevention, rehabilitation, as well as a number of potential neurologic benefits that may be relevant to sports. Studies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 99 publications
(140 reference statements)
0
11
0
3
Order By: Relevance
“…The absence of significant treatment interactions in our study, despite observable changes in mean values, contributes to the ongoing discussion on the role of these supplements in exercise performance enhancement. This underscores the importance of nuanced interpretation of ergogenic aids, as Hall et al (2021) posited, suggesting that these supplements may have more subtle and context-dependent effects on physical performance than previously understood [ 56 ]. Our comprehensive analysis endorses a cautious approach to declaring the efficacy of CN and CAF as performance enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of significant treatment interactions in our study, despite observable changes in mean values, contributes to the ongoing discussion on the role of these supplements in exercise performance enhancement. This underscores the importance of nuanced interpretation of ergogenic aids, as Hall et al (2021) posited, suggesting that these supplements may have more subtle and context-dependent effects on physical performance than previously understood [ 56 ]. Our comprehensive analysis endorses a cautious approach to declaring the efficacy of CN and CAF as performance enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…Creatine has an effect on muscle structure and strength, while stimulating energy generation during vigorous physical exercise. This increases physical performance and extends the time of effective physical exertion [ 25 , 26 , 28 , 30 , 31 , 32 , 33 , 34 ]. On the other hand, the scale of probiotic use was low.…”
Section: Discussionmentioning
confidence: 99%
“…The literature available on the functional properties of individual supplements, including ergogenic aids, is highly extensive [ 11 , 12 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In numerous studies, the use of supplements by athletes of various disciplines is described in detail [ 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that when creatine was used as a dietary supplement, the amount of lean meat and exercise ability increased during short-term with high-intensity exercise. In addition to increased strength, postexercise injury and neurological recovery related to exercise can be achieved by supplementing creatine [ 30 ]. Studies have shown that cinnamic acid and its derivatives extracted from plants have antibacterial effects on many microorganisms [ 31 ], but there was no research on extracting this substance from animals.…”
Section: Discussionmentioning
confidence: 99%